2017
DOI: 10.1016/j.jfs.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Competition, efficiency and soundness in European life insurance markets

Abstract: This paper provides cross-country evidence on the association between soundness and competition in the life insurance industry where competition is measured by the Boone indicator. We analyze 10 European Union (EU) life insurance markets over the postderegulation period 1999-2011. The results indicate that competition increases the soundness of the EU life insurance markets but incentivizes EU life insurers to hold less capital. Since the Boone indicator measures competition based on the reallocation of profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 42 publications
2
48
0
1
Order By: Relevance
“…Results also show that bank size measured using total assets is significantly negatively related to efficiency. In the case of bank soundness, our results are partly consistent with what other researchers (Cummins et al 2017;Schaeck & Cihak 2008) have found. Thus, competition using the Boone indicator is negatively related to the Z score, implying that competition enhances bank soundness and these results support the prudent and efficient management hypothesis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Results also show that bank size measured using total assets is significantly negatively related to efficiency. In the case of bank soundness, our results are partly consistent with what other researchers (Cummins et al 2017;Schaeck & Cihak 2008) have found. Thus, competition using the Boone indicator is negatively related to the Z score, implying that competition enhances bank soundness and these results support the prudent and efficient management hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…The argument is that more efficient banks have lower risks and are sounder than their less efficient counterparts. The negative value of the Boone indicator and the positive value of the Lerner index support this hypothesis in this South African banking sample.Schaek and Cihak, using data from Europe and the United States, as well asCummins et al (2017), using European life insurance markets found similar results. Thus, an increase in the Lerner index signals a fall in the level of competition and since we found a negative relationship between competition and efficiency, this means an increase in efficiency which increases bank soundness.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…In this model, the absence of concentration, it will lead to the presence of oligopolistic industry structure, whereby it is characterised as lacking of competition. Earlier research on the insurance market has revealed that the efficiency of insurers tends to be poor and competition between insurers is not strong (Cummins, RubioMisas, & Vencappa, 2017;Lee, Cheng, Nassir, & Razak, 2018). Thus, these studies propose that, the study on competition is needed to comprehend the analysis on efficiency and productivity.…”
Section: Competitivenessmentioning
confidence: 99%
“…Therefore, it is also important to investigate the market structure of Takaful insurance in Malaysia to ensure the healthy growth of Takaful business. Lastly, merely assessing the competitiveness of insurance will only yield minimal implications; it is advisable to examine the relationship between efficiency and competitiveness, because intense competition will shorten the long-term relationships between insurers and policyholders and result in increased inefficiency of insurers (Alhassan & Biekpe, 2016;Cummins, Rubio-Misas, & Vencappa, 2017). In this vein, this paper attempts to investigate the effects of efficiency on the competitiveness of Takaful insurance in Malaysia and to examine whether the efficiency of Takaful insurance operators in Malaysia could be enhanced in such a way as to improve competition within the Takaful industry but still make it possible to keep the system from evolving into a perfectly competitive Takaful industry, thereby securing the financial stability of Islamic finance.…”
Section: Introductionmentioning
confidence: 99%